2013
DOI: 10.1016/j.actamat.2013.03.043
|View full text |Cite
|
Sign up to set email alerts
|

In situ study of granular micromechanics in semi-solid carbon steels

Abstract: This is the accepted version of the paper.This version of the publication may differ from the final published version. Permanent repository link AbstractThe granular micromechanics of semi-solid steel at 80% solid are studied by synchrotron radiography. A particulate soil mechanics approach to image analysis shows that deformation occurs by the translation and rotation of quasi-rigid grains under the action of contact forces, and that the changes in directional fabric and grain-grain contacts occur by mechani… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
28
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 36 publications
(29 citation statements)
references
References 50 publications
1
28
0
Order By: Relevance
“…The synchrotron experimental procedure has been described in previous publications [8,14,16] and is schematized in Figure 1. It consisted of the specimen being held in a square, hollowed out, 200 µm thick Al2O3 mould sandwiched in between two 100 µm thick sapphire plates and held in between two boron nitride plates.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The synchrotron experimental procedure has been described in previous publications [8,14,16] and is schematized in Figure 1. It consisted of the specimen being held in a square, hollowed out, 200 µm thick Al2O3 mould sandwiched in between two 100 µm thick sapphire plates and held in between two boron nitride plates.…”
Section: Methodsmentioning
confidence: 99%
“…In order to directly image the microstructural response to load, we use synchrotron radiography building on the techniques developed for steel solidification by Yasuda et al [12]. We study deformation under conditions of fully-fed deformation and deformation with inadequate feeding with the following specific aims: (i) to identify and quantify the deformation mechanisms, (ii) to compare the observed mechanisms with those assumed in models of the continuous casting process and those measured in steels at lower solid fraction previously [13][14][15], and (iii) to develop an understanding of how shear deformation can generate macrosegregation and cracking during the final stages of solidification.…”
Section: Introductionmentioning
confidence: 99%
“…In the case of a silt, the diversity of particle shape ranging from almost spherical to needle-like grains and the wide range of grain sizes, makes the segmentation process more complex. Paniagua et al (2014) and Fonseca et al (2013c) describe the use of manual techniques to quantify the characteristics of individual grains for the case of lower quality images where the edges of the grains are difficult to identify and an automated process is not viable. In the present study, the high quality of the EPMA images has enabled the development of an automated process to segment the images.…”
Section: Methodsmentioning
confidence: 99%
“…28,29 However, direct in situ imaging has shown that semisolid alloys often deform by shear-induced dilation. 23,24,30,31 As an example, Fig. 2c shows a local region of microstructure where the configuration of four grains and the loading direction are similar to the geometry in Fig.…”
Section: General Phenomenamentioning
confidence: 99%
“…Therefore, in situ studies were performed on semisolid alloys of a variety of solid fractions and crystal morphologies to study the micromechanics in a range of semisolid alloys. 23,24,31 These studies have found that, during loading in the shear cell, the microstructural response to load shares common features whenever the partially solid alloy consists of numerous grains in mechanical contact and there is sufficient interstitial liquid to feed volumetric strains. These common features are as follows:…”
Section: General Phenomenamentioning
confidence: 99%